Study of ball screw system preload monitoring during operation based on the motor current and screw-nut vibration. (15th September 2019) - Nguyen, Tung Lam; Ro, Seung-Kook; Park, Jong-Kweon
Highlights: A discrete dynamic modeling of a ball screw drive system for investigating the relationship between preload level and axial natural frequency of the ball screw system is proposed. Preload level can be estimated from the axial natural frequency of the ball screw system and the current working table displacement. Signal processing method for measuring the real time preload level of ball screw drive system in operational mode is proposed. Three ranges of preload level (high, normal, low preload) are effectively and intuitively monitored during operational mode. (Revision) An impact test results was added to verify predicted natural frequency of axial mode of table. Abstract: In this paper, we propose a method to monitor the preload of an operational ball screw drive system mostly used in CNC machine tools by evaluating the natural frequency of the screw nut in the axial direction and the corresponding working table displacement. First, we derived a discrete dynamic model and used it to study the variation in the ball screw system preload. Second, we proposed a method for monitoring the ball screw preload in operational mode via the motor current signal and the screw nut axial vibration signal. We apply this method by acquiring and analyzing the signals from the system as it undergoes a transition in its motion, then compose the frequency response function (FRF) of the ball screw system. This enables us to detect the axial natural frequency of the ball screw drive system. The ball screw preload is then calculated and monitored as the system is operational. We provide an efficient and intuitive method to monitor the variation in preload level of an operational ball screw system. This method can be used as an indicator of the health status of the drive system in particular, as well as for the entire machine tool in general.